Factors affecting readmission rates after pancreatectomy. (16th February 2020) - Hue, Jonathan J.; Navale, Suparna; Schiltz, Nicholas; Koroukian, Siran M.; Ammori, John B.
Abstract: Background: Pancreatectomy is a complex operation with a historic readmission rate of approximately 20%. Hospital readmissions lead to increased patient and health system costs, morbidity, and mortality making them a topic of great interest. The objective of this study was to identify factors associated with readmission after pancreatectomy in order to target areas for improvement. Methods: Pancreatectomy procedures for malignancy in adults from 2005 to 2011 were identified in the California State Inpatient Database. Descriptive analysis was conducted to evaluate the association between baseline variables and readmission status. Logistic regression models were developed to determine whether the bivariate associations identified persisted after adjusting for patient characteristics. Results: Of the 4262 patients who underwent a pancreatectomy, 843 (19.8%) were readmitted within 30 days. Readmission rates by year did not vary over the study period. Results from multivariable analysis showed that males, Hispanics, Medicare recipients, patients with an initial length of stay >11 days, patients who were discharged to a skilled nursing facility, and those with chronic anemia were more likely to be readmitted compared to those without these characteristics. The majority of readmissions occurred within 15 days after discharge. Conclusions: Readmissions after pancreatectomy are multifactorial. Preoperative optimization, minimizing postoperative complications, and assuring patients have been evaluated by a multidisciplinary team may reduce the readmission rate. Abstract : Highlight Pancreatectomy for malignancy has a high readmission rate. Hue and colleagues showed that Medicare patients, those with a prolonged initial length of stay, and those discharged to a skilled nursing facility are more likely to be readmitted. Postoperative multidisciplinary team evaluation may help reduce preventable readmissions.